2014
DOI: 10.1108/sbm-09-2011-0075
|View full text |Cite
|
Sign up to set email alerts
|

An empirical assessment of factors affecting the brand-building effectiveness of sponsorship

Abstract: Purpose – The purpose of this study is to assess, in two different live sponsorship environments, the contribution of sponsorship to consumer-based brand equity. Design/methodology/approach – The study adopts a quantitative survey methodology, employing self-administered questionnaires at two UK sporting events (athletics and cricket). To isolate the impact of sponsorship, questionnaires were also distributed to comparison sample groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 53 publications
3
28
0
11
Order By: Relevance
“…Exposure on match day has a positive effect on sponsor brand loyalty (Vale et al, 2009), but it is quite important to strive for a balance between number of sponsors and potential turnover when attracting sponsors. This argument is equally important for sponsors who benefit more, in terms of brand equity, from more exclusive sponsor arrangements (Donlan, 2014). Exposure effects are also depending on previous brand experiences resulting in that exposure of a known brand on match day will have a stronger effect than for a less known brand (Breuer and Rumpf, 2011).…”
Section: Football Clubs As Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure on match day has a positive effect on sponsor brand loyalty (Vale et al, 2009), but it is quite important to strive for a balance between number of sponsors and potential turnover when attracting sponsors. This argument is equally important for sponsors who benefit more, in terms of brand equity, from more exclusive sponsor arrangements (Donlan, 2014). Exposure effects are also depending on previous brand experiences resulting in that exposure of a known brand on match day will have a stronger effect than for a less known brand (Breuer and Rumpf, 2011).…”
Section: Football Clubs As Mediatorsmentioning
confidence: 99%
“…Furthermore, perceived alignment of sponsor and sponsored club is one central dimension in the "Brand Image Transfer" model proposed by Smith (2004). This strategic fit between the sponsor and sponsee has in a number of studies been shown to be an important dimension in generating a favourable attitude towards the sponsor (Becker-Olsen and Hill, 2006;Cornwell et al, 2005;Donlan, 2014;Grohs et al, 2004;Lacey and Close, 2013;Woisetschläger et al, 2017;Zaharia et al, 2016). A lack of fit, e.g.…”
Section: Football Clubs As Mediatorsmentioning
confidence: 99%
“…This means that sponsorship improves the buying power of the sponsor company (Biscaia et al, 2017) through the positive financial indicators such as stock prices, property rights, and the brand value (Kim, Trail, Woo, & Zhang, 2011). In details, the sports sponsorship has a positive role in enhancing, promoting, and improving the brand loyalty (Donlan, 2014). It is clearly shown that sports sponsorship has a positive impact on the awareness , impression, and loyalty of the sponsor company and its brands (Biscaia et al, 2017) as well the brand enhancement (Limba & Jurkutė, 2013) and this will improve the buying behavior toward their products (Pijkeren, 2010).…”
Section: Brand Enhancement and Buying The Brandmentioning
confidence: 99%
“…In previous studies the influence of certain communication tools on brand equity and brand value was explored (Donlan, 2014); e.g. Kim (2001) focussed on advertising, Alexander (2009) and Henseler et al (2011) on sponsorship and both were compared by Hoek et al (1997) and Cornwell (2013), who discussed the current state of research on sponsorship-linked marketing, also referring to sport.…”
Section: Brand Management and Sport Sponsorshipmentioning
confidence: 99%